Bikabepo Wabidaka Learning Media to Cultivate Students Character - Fuadi, Ali Ma'shum; Sutopo, Anam; Desstya, Anatri; Rahmawati, Laili Etika; Fauzianti, Endang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The use of media in learning in schools is not the same, but must be adapted to the characteristics of each school, including at the elementary school level. One of the learning media that is suitable for use at the elementary school level is the Bikabepo Wabidaka learning media. This research is motivated by the lack of attitudes displayed by elementary school students in the learning process of civic education, so learning media is needed to cultivate the character of these students, one of which is through the Bikabepo Wabidaka media. The purpose of this study is to identify the development of learning media Bikabepo Wabidaka in elementary schools. The research method used is Research & Development using Borg & Gall development procedures which include: potential problems, data collection, product design, design validation, and design revision. The instrument used is a media feasibility validation questionnaire sheet. The results obtained, it can be said that the Bikabepo Wabidaka learning media in civic education lessons that have been developed deserves to be tested further to see the effectiveness in learning and building student character in elementary schools.